Former Yugoslav Republic of Macedonia : 2010 Article IV Consultation and Request for an Arrangement Under the Precautionary Credit Line. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, economic recovery and growth of Macedonia are discussed. In the financial sector, nonperforming loans (NPLs) rose, and bank profitability declined as a result of the crisis. Executive Directors agreed with the thrust of the staff appraisal. Directors were encouraged by the overall healthy condition of the financial system. The need to accelerate structural reforms and strengthen public infrastructure to raise productivity and help reduce high unemployment is encouraged. Macedonia met the Precautionary Credit Line (PCL) qualification requirements.